Lead optimization-hit expansion of new asymmetrical pyridinium/quinolinium compounds as choline kinase α1 inhibitors. (24th July 2018) - Rubbini, Gianluca; Buades-Martín, Ana Begoña; Kimatrai-Salvador, María; Entrena, Antonio; Gallo-Mezo, Miguel Ángel; Ríos-Marco, Pablo; Marco, Carmen; Mattiuzzo, Elena; Bortolozzi, Roberta; Mariotto, Elena; Greco, Francesco Antonio; Macchiarulo, Antonio; et al.
Aim: Choline kinase α inhibitors represent one of the newest classes of cytotoxic drugs for cancer treatment, since aberrant choline metabolism is a characteristic shared by many human cancers.Results: Here, we present a new class of asymmetrical pyridinium/quinolinium derivatives developed and designed based on drug optimization.Conclusion: Among all compounds described here, compound8, bearing a 7-chloro-4N-methyl-p-chloroaniline quinolinium moiety, exhibited the greatest inhibitory activity at the enzyme (IC50 = 0.29 μM) and antiproliferative activity in cellular assays (GI50 = 0.29–0.92 μM). Specifically, compound8 strongly induces a cell-cycle arrest in G1 phase, but it does not significantly induce apoptosis while causing senescence in the MDA-MB-231 cell line. Graphical abstracts: